Indigenous Digital Art as Politics in Australia. Issue 3 (3rd July 2017) - Bessant, Judith; Watts, Rob
ABSTRACT: This essay contributes to discussions about Indigenous politics and debates about contemporary democracy. It uses a case study of video art produced by young indigenous people and a community development organisation in the Pilbara, Australia. Those involved in the project use digital media under the auspices of the Big hART Yijala Yala Project to produce an interactive comic series. The essay addresses the following questions: Do contemporary community development projects play a conservatising role serving the interests of a neoliberal polity? Given the long-standing practice of representing modern media as a vehicle for western domination what, if anything, do these projects imply about the political relations between Aboriginal and non-indigenous Australians? Are Indigenous media and cultural work inherently political? What conceptions of the political are at stake in such arguments? We focus on how certain groups of young people use new media, and how their activities are political. The argument is that Indigenous media like these are 'inherently political' because they are about efforts to reclaim the images of indigenous peoples for themselves.